(untitled) (Research, Society and Development, 2022)
Objective: To identify the main problems encountered by nursing professionals when performing the necessary procedures in CPA. Methodology: This is an integrative literature review, based on the Latin American and Caribbean Literature on Health Sciences (LILACS), the Scientific Electronic Library Online (SCIELO) and PubMed, covered by the Virtual Library in Health (VHL). Articles written in Portuguese and English, published between 2012 and 2021, were used. Results: A total of 2,347 articles were found, after methodological rigor through the inclusion and exclusion criteria, 13 articles were selected, 7 in LILACS, 4 in PubMed and 2 in SCIELO. The studies highlighted the importance of training aimed at teams to obtain a quick response to a CPA. Conclusion: In view of the study, it was possible to observe that the cardiopulmonary resuscitation (CPR) maneuver is effective and reduces the level of mortality if performed quickly, and correctly following the necessary technique step-by-step. It is worth emphasizing the importance of the nurse in the rapid identification and implementation of the CPR protocol, thus preserving the quality of the procedure.